A26 Basic Understanding: The Role Of Abnormal Htt Accumulation. (17th September 2014) - Ochaba, J; O'Rourke, JG; Monteys, AM; Lee, J; Steffan, JS; Davidson, B; Thompson, LM
Abstract : Diverse cellular processes are impacted by expression and accumulation of mutant HTT (mHTT) and post-translational modifications of HTT contribute to normal and aberrant protein levels and function. A number of cellular processes are involved in accumulation of mutant HTT. One of these, SUMO modification, involves the covalent attachment of SUMO (Small Ubiquitin-like Modifier) to specific lysine residues and modulates protein activity and clearance. The SUMO pathway is highly conserved and is implicated in HD and other neurodegenerative diseases including spinocerebellar ataxias, Alzheimer's disease (AD), Parkinson's disease (PD), and Amyotrophic Lateral Sclerosis (ALS). We have shown that a single E3 SUMO ligase, PIAS1, modulates both SUMO-1 and 2/3 modification of mHTT in cells, raising the possibility that modulation of this enzyme could provide a selective therapeutic target. In recent studies, we show that instrastriatal viral delivery of PIAS1 miRNA in R6/2 mice significantly reduces HD-like behavioural phenotypes. Biochemical analysis reveals a reduction of accumulated SUMO-1/2, Ubiquitin modified proteins, and insoluble HMW HTT species. PIAS proteins are relevant in transcriptional regulation (mainly negative) of pathways including proinflammatory cytokine signalling and innate immune response. PIAS1 interacts with a wide range of proteins and structurally diverse molecules and we show that it may act as an important negative regulator of signalling cascades that regulate inflammation and protein clearance networks in HD. The pathways identified here in the context of HD and targeting gene-specific regulators such as PIAS1 may represent novel therapeutic strategies that impact mutant HTT levels and provide insight into mechanisms underlying HD.